Pengaruh Trust, Gaya Kepemimpinan, Sistem Pengendalian Manajemen dan Kompetensi Sumber Daya Manusia terhadap Kinerja Keuangan Koperasi (Studi Kasus Pada Koperasi di Kecamatan Selaparang Kota Mataram) - Baiq Titin Fitriani; L Takdir Jumaidi (Jurnal Akuntansi dan Keuangan Daerah, 2022)
This study aims to analyze the influence of trust, leadership style, management control systems and human resource competencies on the financial performance of cooperatives in Selaparang District of Mataram City. This research method uses quantitative research methods with primary data obtained from a Likert scale questionnaires. The population used is all members of 119 cooperatives in Selaparang district of Mataram City. The sample of this research is the finance staff and supervisors whose numbers are determined using the Slovin formula so that a total of 98 people is obtained as the study sample. The results of this study indicate that (1) Quality of Trust has a significant negative effect on the financial performance of cooperatives in Selaparang district of the Mataram city. (2) Leadership style has a significant positive effect on the financial performance of cooperatives in Selaparang district of the Mataram city. (3) The management control system has a significant positive effect on the financial performance of cooperatives in Selaparang district of the Mataram city. (4) Human resource competence has a significant positive effect on the financial performance of cooperatives in Selaparang district of the Mataram city